2016
DOI: 10.1371/journal.pone.0162137
|View full text |Cite
|
Sign up to set email alerts
|

High IFN-γ Release and Impaired Capacity of Multi-Cytokine Secretion in IGRA Supernatants Are Associated with Active Tuberculosis

Abstract: Interferon gamma (IFN-γ) release assays (IGRAs) detect Mycobacterium tuberculosis (Mtb) infection regardless of the active (ATB) or latent (LTBI) forms of tuberculosis (TB). In this study, Mtb-specific T cell response against region of deletion 1 (RD1) antigens were explored by a microbead multiplex assay performed in T-SPOT TB assay (T-SPOT) supernatants from 35 patients with ATB and 115 patients with LTBI. T-SPOT is positive when over 7 IFN-γ secreting cells (SC)/250 000 peripheral blood mononuclear cells (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Another study showed that mycobacterium-specific CD8 þ T cells can secrete IFN-c without help from CD4 þ T cells. 15 Our results are in agreement with those of previous studies, [16][17][18] which indicated that IFN-c release was clearly elevated during MTB infection. Furthermore, we found that 28 pg/mL of IFN-c had advantages over the recommended cut-off value of 14 pg/mL for TB- IGRA.…”
Section: Discussionsupporting
confidence: 91%
“…Another study showed that mycobacterium-specific CD8 þ T cells can secrete IFN-c without help from CD4 þ T cells. 15 Our results are in agreement with those of previous studies, [16][17][18] which indicated that IFN-c release was clearly elevated during MTB infection. Furthermore, we found that 28 pg/mL of IFN-c had advantages over the recommended cut-off value of 14 pg/mL for TB- IGRA.…”
Section: Discussionsupporting
confidence: 91%
“…Blood was collected for the IGRA and analyzed with the Quan-tiFERON Gold In-Tube assay (Cellestis/Qiagen, Dusseldorf, Germany). The IGRA method quantifies the IFN-γ released after the incubation of blood with a cocktail of peptides derived from ESAT-6, CFP-10, and TB7.7 (Rv2654c) antigens [24]. The IGRA was considered positive if the level of IFN-γ was 0.35 IU/mL or more [24].…”
Section: Tst and Igramentioning
confidence: 99%
“…Interleukin-2 (IL-2) was the most extensively investigated alternative immunological biomarker (Hur et al, 2015;Wergeland et al, 2016;Won et al, 2017;La Manna et al, 2018;Lesosky et al, 2019). IFN-γ inducible protein or CXCL-10 (IP-10) (Jeong et al, 2015;Wergeland et al, 2016;Villar-Hernández et al, 2017) and monokine induced by IFN-γ or CXCL-9 (MIG) (Frahm et al, 2011;Carrère-Kremer et al, 2016)…”
Section: Introductionmentioning
confidence: 99%